Solar cell electrode and method of making same, solar cell, battery assembly, and photovoltaic system
Patent Information
- Application Number
- CN202610931879.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-25
- Publication Date
- 2026-09-08
AI Technical Summary
[0003]传统的太阳能电池电极通常采用银电极,银电极的导电性较好,但其成本高,使得太阳能电池的整体生产成本偏高
[0007] The aforementioned solar cell electrode includes large alloy particles of a specific diameter and small alloy particles of a specific diameter. Both the large and small alloy particles contain copper and silver elements, and the number of particles with a diameter of 1.5μm to 3.5μm in the large alloy particles has a specific proportion. The large alloy particles in the solar cell electrode serve as the conductive body, while the small alloy particles serve as fillers between the large alloy particles. By matching the sizes of the large and small alloy particles, not only can the cost of the battery be reduced, but the good conductivity of the solar cell electrode can also be ensured. This can reduce the production cost of the solar cell while ensuring the photoelectric conversion efficiency of the solar cell.
Smart Images

Figure CN122719221A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of photovoltaic technology, and in particular to solar cell electrodes and their preparation methods, solar cells, battery modules and photovoltaic systems. Background Technology
[0002] Electrodes in solar cells are typically formed by applying electrode paste to the cell and then sintering it at high temperatures. Sintering allows the metal in the electrode paste to form a low-resistance ohmic contact with the silicon substrate, eliminating the metal-semiconductor barrier, reducing series resistance losses, and improving the fill factor of the solar cell.
[0003] Traditional solar cell electrodes typically use silver electrodes, which offer good conductivity but are expensive, contributing to the overall high production cost of solar cells. Therefore, developing a solar cell electrode that offers both good conductivity and lower cost has become a crucial research direction in this field. Summary of the Invention
[0004] Based on this, this application provides a solar cell electrode and its fabrication method, a solar cell, a battery module, and a photovoltaic system. This solar cell electrode exhibits good conductivity and low cost.
[0005] According to a first aspect of this application, a solar cell electrode is provided, comprising large alloy particles and small alloy particles, wherein both the large alloy particles and the small alloy particles comprise copper and silver.
[0006] The diameter of the large alloy particles is larger than that of the small alloy particles. The diameter of the large alloy particles is 1μm to 6μm, and the diameter of the small alloy particles is 0.1μm to 0.7μm. Among the large alloy particles, the proportion of particles with a diameter of 1.5μm to 3.5μm is 30% to 70%.
[0007] The aforementioned solar cell electrode includes large alloy particles of a specific diameter and small alloy particles of a specific diameter. Both the large and small alloy particles contain copper and silver elements, and the number of particles with a diameter of 1.5μm to 3.5μm in the large alloy particles has a specific proportion. The large alloy particles in the solar cell electrode serve as the conductive body, while the small alloy particles serve as fillers between the large alloy particles. By matching the sizes of the large and small alloy particles, not only can the cost of the battery be reduced, but the good conductivity of the solar cell electrode can also be ensured. This can reduce the production cost of the solar cell while ensuring the photoelectric conversion efficiency of the solar cell.
[0008] In some embodiments, the number of particles with a diameter of 1.5 μm to 3.5 μm accounts for 50% to 70% of the large alloy particles.
[0009] In some embodiments, the proportion of particles with a diameter of 0.2 μm to 0.4 μm in the small alloy particles is 70% to 75%.
[0010] In some embodiments, based on the total mass of the solar cell electrode, the sum of the mass fractions of the large alloy particles and the small alloy particles is greater than 60%, optionally greater than 80%, and further optionally greater than 95%.
[0011] In some embodiments, the total mass of the large alloy particles and the small alloy particles is used as a basis, with the large alloy particles accounting for 30% to 70% of the mass and the small alloy particles accounting for 30% to 70% of the mass.
[0012] In some embodiments, the mass fraction of copper in the large alloy particles is greater than the mass fraction of silver.
[0013] In some embodiments, the mass fraction of copper in the large alloy particles is 55% to 70%, and the mass fraction of silver is 25% to 40%.
[0014] In some embodiments, the mass fraction of copper in the small alloy particles is less than the mass fraction of silver.
[0015] In some embodiments, the small alloy particles contain 26% to 43% copper and 52% to 68% silver by mass.
[0016] In some embodiments, the solar cell electrode has a recessed portion and a protruding portion, wherein the height of the protruding portion is 40 μm to 60 μm and the height of the recessed portion is 5 μm to 30 μm.
[0017] According to a second aspect of this application, a method for preparing a solar cell electrode according to the first aspect of this application is provided, comprising the following steps:
[0018] An electrode paste is provided, the electrode paste comprising silver particles, copper particles and a mixture of glass and organic matter, wherein the mass ratio of the silver particles, the copper particles and the mixture of glass and organic matter is (1~3):(2~7):(90~95);
[0019] The electrode paste is coated and sintered to obtain the solar cell electrode.
[0020] In some embodiments, the silver particles in the electrode slurry have a particle size of 0.1 μm to 10 μm.
[0021] In some embodiments, the copper particles in the electrode slurry have a particle size of 20 μm to 70 μm.
[0022] In some embodiments, the sintering temperature is 150°C to 350°C.
[0023] According to a third aspect of this application, a solar cell is provided, comprising one or more of the solar cell electrodes prepared by the methods of the first aspect of this application and the second aspect of this application.
[0024] According to a fourth aspect of this application, a battery assembly is provided, including the solar cell of the third aspect of this application.
[0025] According to a fifth aspect of this application, a photovoltaic system is provided, including the solar cell of the third aspect of this application. Attached Figure Description
[0026] To better describe and illustrate the embodiments or examples provided in this application, reference may be made to one or more accompanying drawings. Additional details or examples used to describe the drawings should not be considered as limiting the scope of any of the disclosed applications, the currently described embodiments or examples, or the best mode of conduct of these applications as currently understood. Furthermore, the same reference numerals denote the same parts throughout the drawings. In the drawings:
[0027] Figure 1 This is a scanning electron microscope image of a solar cell electrode according to an embodiment of this application.
[0028] Figure 2 This is a side view of a solar cell electrode according to one embodiment of this application.
[0029] Explanation of reference numerals in the attached figures:
[0030] 10. Solar cell electrode; C. Recessed part; D. Protruding part; E. Large alloy particle; F. Small alloy particle. Detailed Implementation
[0031] To make the above-mentioned objectives, features, and advantages of this application more apparent and understandable, a detailed description of specific embodiments of this application is provided below. Many specific details are set forth in the following description to provide a thorough understanding of this application. However, this application can be implemented in many other ways different from those described herein, and those skilled in the art can make similar modifications without departing from the spirit of this application. Therefore, this application is not limited to the specific embodiments disclosed below.
[0032] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs. The terminology used herein is for the purpose of describing particular embodiments only and is not intended to be limiting of the application. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.
[0033] One embodiment of this application provides a solar cell electrode, see [link to previous application]. Figure 1 and Figure 2 The solar cell electrode 10 includes a mixture of large alloy particles E and small alloy particles F, both of which contain copper and silver. The diameter of the large alloy particles E is larger than that of the small alloy particles F, with the diameter of the large alloy particles E being 1 μm to 6 μm and the diameter of the small alloy particles F being 0.1 μm to 0.7 μm. Among the large alloy particles, the proportion of particles with a diameter of 1.5 μm to 3.5 μm is 30% to 70%.
[0034] The aforementioned solar cell electrode 10 includes large alloy particles E of a specific diameter and small alloy particles F of a specific diameter. Both the large alloy particles E and the small alloy particles F contain copper and silver elements, and the number of particles with a diameter of 1.5μm to 3.5μm in the large alloy particles has a specific proportion. The large alloy particles E in the solar cell electrode 10 serve as the conductive body, and the small alloy particles F serve as fillers between the large alloy particles E. By matching the sizes of the large alloy particles and the small alloy particles, not only can the cost of the battery be reduced, but the good conductivity of the solar cell electrode 10 can also be guaranteed. This can reduce the production cost of the solar cell while ensuring the photoelectric conversion efficiency of the solar cell.
[0035] It is understandable that the diameter of the large alloy particles E in the solar cell electrode 10 can be 1μm, 1.2μm, 1.5μm, 1.8μm, 2μm, 2.2μm, 2.5μm, 2.8μm, 3μm, 3.2μm, 3.5μm, 3.8μm, 4μm, 4.2μm, 4.5μm, 4.8μm, 5μm, 5.2μm, 5.5μm, 5.8μm, 6μm, or any value within the range formed by any two of the above values. The diameter of the small alloy particles F in the solar cell electrode 10 can be 0.1μm, 0.15μm, 0.2μm, 0.25μm, 0.3μm, 0.35μm, 0.4μm, 0.45μm, 0.5μm, 0.55μm, 0.6μm, 0.65μm, 0.7μm, or any value within the range formed by any two of the above values. In the large alloy particles E, the percentage of particles with a diameter of 1.5μm to 3.5μm can be 30%, 32%, 35%, 38%, 40%, 42%, 45%, 48%, 50%, 52%, 55%, 58%, 60%, 62%, 65%, 68%, 70%, or any value within the range formed by any two of the above values.
[0036] It should be noted that the particle size and elemental composition of the aforementioned large alloy particles E and small alloy particles F can be adjusted by modifying the composition of the electrode paste for solar cells. For example, the particle size, dosage ratio, and respective proportions of silver and copper particles in the electrode paste can be adjusted.
[0037] The large alloy particles E and small alloy particles F can be statistically analyzed using the following method: Scanning electron microscopy (SEM) is used to perform microscopic inspection of the solar cell electrode 10. One hundred particles within the SEM field of view are selected for particle size measurement to obtain the particle size distribution. This allows determination of the number of large alloy particles E (diameter 1 μm–6 μm), the number of small alloy particles F (diameter 0.1 μm–0.7 μm), and the proportion of particles with diameters of 1.5 μm–3.5 μm among the large alloy particles E. Energy-dispersive X-ray spectroscopy (EDS) can then be used to obtain the elemental composition and atomic ratios of the large alloy particles E and small alloy particles F.
[0038] In some embodiments, the proportion of particles with a diameter of 1.5 μm to 3.5 μm in the large alloy particles E is 50% to 70%. Controlling the proportion of particles with a diameter of 1.5 μm to 3.5 μm in the large alloy particles E of the solar cell electrode 10 within the above range is more conducive to improving the conductivity of the solar cell electrode 10.
[0039] In some embodiments, the proportion of particles with a diameter of 0.2 μm to 0.4 μm in the small alloy particles F is 70% to 75%. Controlling the proportion of particles with a diameter of 0.2 μm to 0.4 μm in the small alloy particles F of the solar cell electrode 10 within the above range is more conducive to improving the conductivity of the solar cell electrode 10.
[0040] It is understandable that in small alloy particles F, the proportion of particles with a diameter of 0.2μm to 0.4μm can be 70%, 70.5%, 71%, 71.5%, 72%, 72.5%, 73%, 73.5%, 74%, 74.5%, 75%, or any value within the range formed by any two of the above values.
[0041] In some embodiments, based on the total mass of the solar cell electrode 10, the sum of the mass fractions of the large alloy particles E and the small alloy particles F is greater than 60%, further preferably greater than 80%, and even more preferably greater than 95%. This is more conducive to improving the conductivity of the solar cell electrode 10.
[0042] In some embodiments, based on the total mass of large alloy particles E and small alloy particles F, the mass percentage of large alloy particles E is 30% to 70%, and the mass percentage of small alloy particles F is 30% to 70%. This is more conducive to improving the conductivity of the solar cell electrode 10.
[0043] Understandably, based on the total mass of large alloy particles E and small alloy particles F, the mass percentage of large alloy particles E can be 30%, 32%, 35%, 38%, 40%, 42%, 45%, 48%, 50%, 52%, 55%, 58%, 60%, 62%, 65%, 68%, 70%, or any value within the range formed by any two of the above values. Similarly, the mass percentage of small alloy particles F can be 30%, 32%, 35%, 38%, 40%, 42%, 45%, 48%, 50%, 52%, 55%, 58%, 60%, 62%, 65%, 68%, 70%, or any value within the range formed by any two of the above values.
[0044] In some embodiments, the mass fraction of copper in the large alloy particles E is greater than the mass fraction of silver. This helps to further reduce the cost of the solar cell electrode 10 while maintaining its good conductivity.
[0045] In some embodiments, the mass fraction of copper in the large alloy particles E is 55% to 70%, and the mass fraction of silver is 25% to 40%. It is understood that the mass fraction of copper in the large alloy particles E can be 55%, 56%, 57%, 58%, 59%, 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, 70%, or any value within the range formed by any two of the above values. The mass fraction of silver can be 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, or any value within the range formed by any two of the above values.
[0046] In some embodiments, the mass fraction of copper in the small alloy particles F is less than the mass fraction of silver. This helps to further reduce the cost of the solar cell electrode 10 while maintaining its good conductivity.
[0047] In some embodiments, the mass fraction of copper in the small alloy particles F is 26% to 43%, and the mass fraction of silver is 52% to 68%. It is understood that the mass fraction of copper in the small alloy particles F can be 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, or any value within the range formed by any two of the above values. The mass fraction of silver can be 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, or any value within the range formed by any two of the above values.
[0048] The elemental composition and atomic ratio of large alloy particles E and small alloy particles F can be obtained through EDS, and the mass fraction of each element can be obtained.
[0049] See Figure 2 In some embodiments, the solar cell electrode 10 has a recessed portion C and a protruding portion D, wherein the height h1 of the protruding portion D is 40 μm to 60 μm, and the height h2 of the recessed portion C is 5 μm to 30 μm. The solar cell electrode 10 has a structure with a recessed portion C and a protruding portion D, and the heights of the recessed portion C and the protruding portion D are within the aforementioned ranges. On the one hand, compared to a highly uniform electrode structure, this can save on the amount of electrode paste used, thereby reducing the cost of the solar cell electrode 10. On the other hand, it can ensure that the solar cell electrode 10 has good conductivity and will not significantly affect the photoelectric conversion efficiency of the solar cell.
[0050] It is understood that the height h1 of the protrusion D on the solar cell electrode 10 can be 40μm, 41μm, 42μm, 43μm, 44μm, 45μm, 46μm, 47μm, 48μm, 49μm, 50μm, 51μm, 52μm, 53μm, 54μm, 55μm, 56μm, 57μm, 58μm, 59μm, 60μm, or any value within the range formed by any two of the above values. The height h2 of the recess C on the solar cell electrode 10 can be 5μm, 8μm, 10μm, 12μm, 15μm, 18μm, 20μm, 22μm, 25μm, 28μm, 30μm, or any value within the range formed by any two of the above values.
[0051] It should be noted that the solar cell electrode 10 with the aforementioned structure of the recessed portion C and the protruding portion D can be obtained by adjusting the composition of the electrode paste. For example, the particle size, dosage ratio, and respective proportions of silver and copper particles in the electrode paste can be adjusted. The height of the recessed portion C refers to the distance between the lowest point of the recessed portion C on the upper surface of the solar cell electrode 10 and the lower surface of the solar cell electrode 10; the height of the protruding portion D refers to the distance between the highest point of the protruding portion D on the upper surface of the solar cell electrode 10 and the lower surface of the solar cell electrode 10.
[0052] One embodiment of this application provides a method for preparing the solar cell electrode 10 described above, the method comprising the following steps:
[0053] Step S100: Provide electrode paste, which includes silver particles, copper particles and a mixture of glass and organic matter, with the mass ratio of silver particles, copper particles and the mixture of glass and organic matter being (1~3):(2~7):(90~95).
[0054] Step S200: The above electrode paste is coated and sintered to obtain solar cell electrode 10.
[0055] Controlling the mass ratio of silver particles, copper particles, and the mixture of glass and organic matter in the electrode paste within the aforementioned range is beneficial for forming the specific electrode morphology of the solar cell electrode 10 in this application, as well as the specific composition of large alloy particles E and small alloy particles F in the solar cell electrode 10. By using the above-mentioned electrode paste, after coating and sintering, it is beneficial to obtain the solar cell electrode 10 with the composition and structure of this application, thereby ensuring good conductivity of the solar cell electrode 10 while reducing the production cost of the solar cell electrode 10.
[0056] It should be noted that the above-mentioned electrode paste can be coated on the transparent conductive layer of the solar cell, so that the electrode paste burns through the transparent conductive layer and connects with the doped silicon layer, so that the metal particles in the solar cell electrode 10 form a low-resistance ohmic contact with the semiconductor layer.
[0057] In the aforementioned electrode slurry components, the glass and organic mixture refers to a mixture formed by pre-dispersing glass powder uniformly in an organic carrier. This avoids glass powder agglomeration when directly mixed with silver powder, ensuring uniform electrode contact resistance and high yield. The glass and organic mixture mainly includes inorganic glass powder with a low melting point and an organic carrier. The organic carrier can be a mixture containing one or more of the following: a polymer resin, an organic solvent, and a small amount of additives. In some specific examples, the resin can be ethyl cellulose, acrylic resin, etc., the organic solvent can be terpineol, diethylene glycol butyl ether acetate, etc., and the additives can be thixotropic agents, leveling agents, defoamers, surfactants, etc.
[0058] In some specific examples, the mass fraction of silver particles in the electrode paste is 1%–3%, the mass fraction of copper particles is 2%–7%, and the mass fraction of the glass and organic mixture is 90%–95%. It is understood that the mass fraction of silver particles in the electrode paste can be 1%, 1.2%, 1.5%, 1.8%, 2%, 2.2%, 2.5%, 2.8%, 3%, or any value within the range formed by any two of the above values. The mass fraction of copper particles can be 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, or any value within the range formed by any two of the above values. The mass fraction of the glass and organic mixture can be 90%, 90.5%, 91%, 91.5%, 92%, 92.5%, 93%, 93.5%, 94%, 94.5%, 95%, or any value within the range formed by any two of the above values.
[0059] In some embodiments, the particle size of the silver particles in the electrode paste is 0.1 μm to 10 μm. It is understood that the particle size of the silver particles in the electrode paste can be 0.1 μm, 0.5 μm, 0.8 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, 5.5 μm, 6 μm, 6.5 μm, 7 μm, 7.5 μm, 8 μm, 8.5 μm, 9 μm, 9.5 μm, 10 μm, or any value within the range formed by any two of the above values.
[0060] In some embodiments, the copper particles in the electrode slurry have a particle size of 20 μm to 70 μm. It is understood that the particle size of the copper particles in the electrode slurry can be 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, 55 μm, 60 μm, 65 μm, 70 μm, or any value within the range formed by any two of the above values.
[0061] In some embodiments, the sintering temperature is 150°C to 350°C. It is understood that the sintering temperature can be 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C, 240°C, 250°C, 260°C, 270°C, 280°C, 290°C, 300°C, 310°C, 320°C, 330°C, 340°C, 350°C, or any value within the range formed by any two of the above values.
[0062] One embodiment of this application provides a solar cell, including one or more of the solar cell electrode 10 described above and the solar cell electrode 10 prepared by the method described above. It is understood that this solar cell has the same advantages as the solar cell electrode 10 of this application, having lower production costs and higher photoelectric conversion efficiency.
[0063] It is understood that solar cells can be any existing type of solar cell, including but not limited to silicon heterojunction solar cells (HJT), tunneling oxide passivated contact solar cells (TOPCon), back contact solar cells (BC), and silicon-perovskite tandem solar cells.
[0064] One embodiment of this application provides a battery module including the solar cell described above. Similarly, the battery module of this application also has lower cost and higher photoelectric conversion efficiency.
[0065] The aforementioned battery assembly includes one or more solar cells, which can be selected according to specific application scenarios; furthermore, the aforementioned battery assembly includes multiple solar cells, which are connected in series or in parallel to form a battery cell.
[0066] One embodiment of this application provides a photovoltaic system including the solar cell described above. The photovoltaic system utilizes the solar cell in the aforementioned battery module to directly convert solar radiation energy into electrical energy; further, the aforementioned photovoltaic system is a photovoltaic power generation system.
[0067] Battery modules are the core component of a photovoltaic power generation system. The aforementioned photovoltaic system includes one or more battery modules, which can be selected according to specific application scenarios. Furthermore, when the aforementioned photovoltaic system includes multiple battery modules, the multiple battery modules form a photovoltaic array.
[0068] The aforementioned photovoltaic (PV) systems can be either stand-alone or grid-connected. Stand-alone PV systems include PV arrays, battery banks, charge controllers, power electronic converters (inverters), and loads. Grid-connected PV systems include PV arrays, high-frequency DC / DC boost circuits, power electronic converters (inverters), and system monitoring. Each type of PV system has its own characteristics, and the appropriate system can be selected based on the specific application scenario.
[0069] The following describes embodiments of this application. The embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments used, unless otherwise specified, are all conventional products that can be obtained commercially.
[0070] Example 1:
[0071] (1) Electrode paste preparation
[0072] The electrode slurry is formed by mixing 1 part silver particles with a particle size of 0.4μm to 1.5μm, 5 parts copper particles with a particle size of 20μm to 70μm, and 95 parts glass powder and organic mixture evenly according to the weight.
[0073] (2) Electrode preparation
[0074] The electrode paste prepared in step (1) is coated on the transparent conductive layer (TCO) on the back surface of the heterojunction back contact solar cell (HBC) and sintered at 250°C for 10 min to form an electrode.
[0075] The electrode comprises large alloy particles with diameters ranging from 1 μm to 6 μm and small alloy particles with diameters ranging from 0.1 μm to 0.7 μm. Among the large alloy particles, those with diameters ranging from 1.5 μm to 3.5 μm account for 60% of the total number, and copper accounts for 70% and silver for 28% of the total element mass. Similarly, among the small alloy particles, those with diameters ranging from 0.2 μm to 0.4 μm account for 70% of the total number, and copper accounts for 26% and silver for 68% of the total element mass.
[0076] Example 2:
[0077] This embodiment is basically the same as Embodiment 1, except that:
[0078] In step (1), 1 part silver particles, 6 parts copper particles, and 94 parts glass powder and organic mixture are mixed evenly to form an electrode slurry.
[0079] The parameters of the large and small alloy particles in the electrode are shown in Table 1.
[0080] Example 3:
[0081] This embodiment is basically the same as Embodiment 1, except that:
[0082] In step (1), 2 parts by weight of silver particles, 6 parts by weight of copper particles, and 94 parts by weight of glass powder and organic mixture are mixed evenly to form an electrode slurry.
[0083] The parameters of the large and small alloy particles in the electrode are shown in Table 1.
[0084] Example 4:
[0085] This embodiment is basically the same as Embodiment 1, except that:
[0086] In step (1), 3 parts by weight of silver particles, 7 parts by weight of copper particles, and 94 parts by weight of glass powder and organic mixture are mixed evenly to form an electrode slurry.
[0087] The parameters of the large and small alloy particles in the electrode are shown in Table 1.
[0088] Example 5:
[0089] This embodiment is basically the same as Embodiment 1, except that:
[0090] In step (1), 3 parts by weight of silver particles, 7 parts by weight of copper particles, and 95 parts by weight of glass powder and organic mixture are mixed evenly to form an electrode slurry.
[0091] The parameters of the large and small alloy particles in the electrode are shown in Table 1.
[0092] Example 6:
[0093] This embodiment is basically the same as Embodiment 1, except that:
[0094] In step (1), 2 parts by weight of silver particles, 6 parts by weight of copper particles, and 93 parts by weight of glass powder and organic mixture are mixed evenly to form an electrode slurry.
[0095] The parameters of the large and small alloy particles in the electrode are shown in Table 1.
[0096] Example 7:
[0097] This embodiment is basically the same as Embodiment 1, except that:
[0098] In step (1), 3 parts by weight of silver particles, 2 parts by weight of copper particles, and 95 parts by weight of glass powder and organic mixture are mixed evenly to form an electrode slurry.
[0099] The parameters of the large and small alloy particles in the electrode are shown in Table 1.
[0100] Example 8:
[0101] This embodiment is basically the same as Embodiment 1, except that:
[0102] In step (1), 3 parts by weight of silver particles, 3 parts by weight of copper particles, and 94 parts by weight of glass powder and organic mixture are mixed evenly to form an electrode slurry.
[0103] The parameters of the large and small alloy particles in the electrode are shown in Table 1.
[0104] Example 9:
[0105] This embodiment is basically the same as Embodiment 1, except that:
[0106] In step (1), 3 parts by weight of silver particles, 4 parts by weight of copper particles, and 94 parts by weight of glass powder and organic mixture are mixed evenly to form an electrode slurry.
[0107] The parameters of the large and small alloy particles in the electrode are shown in Table 1.
[0108] Comparative Example 1:
[0109] This embodiment is basically the same as embodiment 1, except that: in step (1), conventional silver paste is used as the electrode paste, which is a mixture of silver particles, glass powder and organic matter.
[0110] The performance data of the solar cells were obtained through IV testing. The electrode compositions and solar cell performance data of the above embodiments and comparative examples are shown in Table 1.
[0111] Table 1
[0112]
[0113] Note: In Table 1, " / " indicates that the test is not conducted or the test is not conducted.
[0114] As shown in Table 1, the electrodes in the various embodiments of this application are composed of large alloy particles and small alloy particles containing copper and silver elements, and the large alloy particles and small alloy particles have specific particle sizes and proportions; this electrode effectively reduces electrode costs while ensuring electrode conductivity. The photoelectric conversion efficiency of solar cells using the electrodes of this application is comparable to, or even higher than, that of cells using conventional silver electrodes.
[0115] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0116] The embodiments described above are merely illustrative of several implementation methods of this application, and while the descriptions are specific and detailed, they should not be construed as limiting the scope of this patent application. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of this application, and these all fall within the protection scope of this application. Therefore, the protection scope of this application should be determined by the appended claims, and the specification and drawings can be used to interpret the content of the claims.
Claims
1. A solar cell electrode, characterized in that, It includes large alloy particles and small alloy particles, both of which contain copper and silver elements; The diameter of the large alloy particles is larger than that of the small alloy particles. The diameter of the large alloy particles is 1μm to 6μm, and the diameter of the small alloy particles is 0.1μm to 0.7μm. Among the large alloy particles, the proportion of particles with a diameter of 1.5μm to 3.5μm is 30% to 70%.
2. The solar cell electrode according to claim 1, characterized in that, In the large alloy particles, particles with a diameter of 1.5μm to 3.5μm account for 50% to 70%.
3. The solar cell electrode according to claim 1, characterized in that, In the small alloy particles, particles with a diameter of 0.2μm to 0.4μm account for 70% to 75%.
4. The solar cell electrode according to claim 1, characterized in that, Based on the total mass of the solar cell electrode, the sum of the mass fractions of the large alloy particles and the small alloy particles is greater than 60%, optionally greater than 80%, and further optionally greater than 95%.
5. The solar cell electrode according to claim 1, characterized in that, Based on the total mass of the large alloy particles and the small alloy particles, the mass percentage of the large alloy particles is 30% to 70%, and the mass percentage of the small alloy particles is 30% to 70%.
6. The solar cell electrode according to any one of claims 1 to 5, characterized in that, The mass fraction of copper in the large alloy particles is greater than the mass fraction of silver.
7. The solar cell electrode according to claim 6, characterized in that, The large alloy particles contain 55% to 70% copper and 25% to 40% silver by mass.
8. The solar cell electrode according to any one of claims 1 to 5 and 7, characterized in that, The mass fraction of copper in the small alloy particles is less than the mass fraction of silver.
9. The solar cell electrode according to claim 8, characterized in that, The small alloy particles contain 26% to 43% copper and 52% to 68% silver by mass.
10. The solar cell electrode according to any one of claims 1 to 5, 7, and 9, characterized in that, The solar cell electrode has a recessed portion and a raised portion, the height of the raised portion being 40μm~60μm and the height of the recessed portion being 5μm~30μm.
11. A method for preparing a solar cell electrode according to any one of claims 1 to 10, characterized in that, Includes the following steps: An electrode paste is provided, the electrode paste comprising silver particles, copper particles and a mixture of glass and organic matter, wherein the mass ratio of the silver particles, the copper particles and the mixture of glass and organic matter is (1~3):(2~7):(90~95); The electrode paste is coated and sintered to obtain the solar cell electrode.
12. The method for preparing a solar cell electrode according to claim 11, characterized in that, The silver particles in the electrode slurry have a particle size of 0.1 μm to 10 μm; And / or, the copper particles in the electrode slurry have a particle size of 20μm to 70μm.
13. The method for preparing a solar cell electrode according to claim 11, characterized in that, The sintering temperature is 150℃~350℃.
14. A solar cell, characterized in that, It includes one or more of the solar cell electrodes prepared by the methods of any one of claims 1 to 10 and any one of claims 11 to 13.
15. A battery assembly, characterized in that, Includes the solar cell of claim 14.
16. A photovoltaic system, characterized in that, Includes the solar cell of claim 14.